Supporting elderly patients in strengthening their personal and spiritual health resources - Stelcer, Bogusław; Bendowska, Aleksandra; Karkowska, Dorota; Baum, Ewa (Frontiers in Psychology, 2023)
Care for the sick, including spiritual support is sometimes called holistic medicine (Sulmasy; 2002, 2009). The term bio-psycho-social-spiritual model is sometimes used to describe this type of therapeutic approach patient-oriented medicine. This report indicates the importance of taking into account the spiritual aspect of life due to its beneficial impact on the coping resources activated and the patient's well-being (Puchalski, Vitillo, Hull, Reller, 2014). Existential and spiritual issues are on the verge of new clinical and research interest in medicine, especially in gerontology, oncology and palliative care. Clinicians focus not only on symptom control but also on spiritual and existential issues such as spirituality, hope and meaning. This paper reviews the topic of spirituality in the context of illness and end-of-life care trying to define spirituality within the context of health resources of the subject. Spirituality is perceived in two of its main components: faith/religious beliefs and spiritual well-being. Especially this second construct is reviewed and described as a health resource.